An investigation on the friction losses between cylinder liner and piston rings - Mohamad Abouchi; Suleyman Basturk (Sustainable Engineering and Innovation, 2022)
Historically, the engine crankcase has been made of gray cast iron due to that material's' high machinability, damping ability, thermal conductivity, and sensible cost. Despite these advantages and the long-term use of gray cast iron, the vehicle manufacturers predominately use cast aluminum as material of choice for the engine block due to aluminum’s density being almost a third of that of gray cast iron, and the aluminum engines have the same durability as gray cast iron while weighing considerably less. However, due to the low wear resistance of aluminum, efforts are needed to improve internal working surfaces such as the use of cast iron cylinder liners or the application of a protective coat is applied to the aluminum surface to increase its resistance. The purpose of this study is to examine which ring materials have the lowest friction with the Twin Wire Arc (TWA) aluminum cylinder liner. An Ansys simulation model accomplishes the experimental work. The steel ring material obviously had the lowest friction with twin wire arc spray aluminum cylinder liner as opposite to the cast iron material which was the worst.